First-line immune checkpoint inhibitors for advanced non-small cell lung cancer with wild-type epidermal growth factor receptor (EGFR) or anaplastic lymphoma kinase (ALK): a systematic review and network meta-analysis - Liu, Tingting; Ding, Silu; Dang, Jun; Wang, Hui; Chen, Jun; Li, Guang (Journal of Thoracic Disease, 2019)
Background: To assess the comparative efficacy and safety of first-line immune checkpoint inhibitors (ICIs) for advanced non-small cell lung cancer (NSCLC) with wild-type epidermal growth factor receptor (EGFR) or anaplastic lymphoma kinase (ALK). Methods: PubMed, Embase, Cochrane Library, Web of Science, and major international scientific meetings were searched for relevant randomized controlled trials. Overall survival (OS) and progression-free survival (PFS) were the primary outcomes and serious adverse events (SAEs) were the secondary outcome of interests and were reported as hazard ratio (HR) or odds ratio (OR) with 95% confidence intervals (CIs). Results: Fourteen trials with 9,570 patients randomized to receive ten ICI-based treatments (including PD-1/PD-L1 and CTLA-4 antibodies and PD-1/PD-L1 with CTLA-4 combination therapies) were included in the meta-analysis. Pembrolizumab combined with chemotherapy (Pem + CT) (HR =0.56, 95% CI: 0.42–0.74) and Pem (HR =0.75, 95% CI: 0.62–0.91) were more effective than CT in terms of OS; Pem + CT was also superior to Pem (HR =0.74, 95% CI: 0.56–0.98), atezolizumab + CT (HR =0.65, 95% CI: 0.50–0.85), ipilimumab + CT (HR =0.65, 95% CI: 0.47–0.89), and nivolumab (HR =0.52, 95% CI: 0.31–0.87). In subgroup analyses, Pem + CT was more effective than CT regardless of PD-L1 expression, while Pem was superior to CT only for PD-L1 with expression ≥50%; Pem + CT showed significant OS advantage over other treatments in patients with non-squamous cell carcinoma (NSCC); ICIs had a comparable efficacy in younger vs. older patients. Based on treatment ranking in terms of OS, Pem + CT had the highest probability (98%) of being the most effective treatment, followed by Pem (70%), with acceptable toxicity limit. Conclusions: Pem + CT seemed to be more effective first-line regimen for advanced NSCLC with wild-type EGFR or ALK, especially for patients with NSCC. However, limitations of the study including methodological quality and immature OS data need to be considered.